Progress towards non-small-cell lung cancer models that represent clinical evolutionary trajectories. Issue 1 (13th January 2021) - Hynds, Robert E.; Frese, Kristopher K.; Pearce, David R.; Grönroos, Eva; Dive, Caroline; Swanton, Charles
Abstract : Abstract : Non-small-cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide. Although advances are being made towards earlier detection and the development of impactful targeted therapies and immunotherapies, the 5-year survival of patients with advanced disease is still below 20%. Effective cancer research relies on pre-clinical model systems that accurately reflect the evolutionary course of disease progression and mimic patient responses to therapy. Here, we review pre-clinical models, including genetically engineered mouse models and patient-derived materials, such as cell lines, primary cell cultures, explant cultures and xenografts, that are currently being used to interrogate NSCLC evolution from pre-invasive disease through locally invasive cancer to the metastatic colonization of distant organ sites.